Interleukin-17A antagonist attenuates radiation-induced lung injuries in mice. (1st March 2014) - Wang, Bao-Zhong; Wang, Li-Ping; Han, Hui; Cao, Fang-Li; Li, Guang-Yao; Xu, Jun-Long; Wang, Xiu-Wen; Wang, Le-Xin
ABSTRACT Objective: To investigate the effect of interleukin-17A (IL-17A) antibodies on radiation-induced lung injuries in mice. Methods: The thorax of 135 mice were divided into Sham (n = 30), radiation control (RC, n = 35), treatment (n = 35, IL-17A-neutralizing antibody, 4 μg/mouse, IV, 4 days per month for 4 months) and placebo group (n = 35) before a single dose irradiation (15 Gy) to the thorax. Inflammation and collagen contents in the lung tissues were examined, and the concentration of IL-17A, TGF-β1, and IL-6 in bronchoalveolar lavage fluid (BALF) were measured. In another 50 animals, 180-day survival rate following the irradiation and treatment was calculated by Kaplan–Meier method. Results: Sixteen weeks after the irradiation and treatment, there was significant inflammatory cell infiltration and interstitial collagen depositions in the radiation control and placebo groups, whereas these changes were relatively mild in the treatment group. The percentage of grade II and III alveolitis in the treatment group (16%, P < .05) was lower than in the RC (72%) or placebo group (64%). The mean Aschcroft fibrosis scores were 2.8 (treatment group), 5.2 (RC), and 4.8 (placebo group), respectively. The scores of treatment group was lower than that of RC (P < .001) or placebo group (P < .001). The IL-17A, TGF-β, and IL-6 concentrations in the treatment group were lower than in the RC and placebo group (P < .01) following the irradiation. The 180-day mortality rate in the treatment group was lower than in the RC group 16.7% versus 75.0%, P < .05). Conclusion: IL-17A antibody treatment alleviates radiation-induced pneumonitis and subsequent fibrosis, and improvise postirradiation survival.